Ni-Catalyzed Reductive Coupling of Alkynes with Aziridines - Zimin, Dmitry P.; Zhang, Liangliang; Janssen-Müller, Daniel; Day, Craig S.; Davies, Jacob; Wakeling, Matthew; Martin, Ruben (Synlett, 2025)
Herein, we describe a Ni-catalyzed regioselective hydroalkenylation of alkynes with aziridines as coupling partners. This protocol allows access to homoallylic amines without recourse to stoichiometric amounts of well-defined organometallic reagents via catalytic regioselective ring-opening of aziridines under mild reaction conditions. The protocol is characterized by its applicability across a wide variety of aziridines or alkynes, including challenging substrate combinations.
Keywords: Alkenylation; Nickel; Reductive coupling; Aziridine; Alkyne